In silico discovery of novel transcription factors regulated by mTOR-pathway activities - Jablonska, Agnieszka; Polouliakh, Natalia (Frontiers in Cell and Developmental Biology, 2014)
The mammalian target of rapamycine (mTOR) pathway is a key regulator of cellular growth, development and ageing, and unraveling its control is essential for understanding life and death of biological organisms. A motif-discovery workbench including nine tools was used to identify transcription factors involved in five basic (Insulin, MAPK, VEGF, Hypoxia, and mTOR core) activities of the mTOR pathway. Discovered transcription factors are classified as process-specific or pathway-ubiquitous with highlights towards their regulating/regulated activities within the mTOR pathway. Our transcription regulation results will facilitate further research on investigating the control mechanism in mTOR pathway.